Multiple epigenetic biomarkers for evaluation of students' academic performance - Lee, Li‐Ching; Su, Ming‐Tsan; Cho, Ying‐Chun; Lee‐Chen, Guey‐Jen; Yeh, Ting‐Kuang; Chang, Chun‐Yen (Genes, brain and behavior, 2019)
Several reports have shown that methyl CpG‐binding protein 2 (MeCP2), brain‐derived neurotrophic factor (BDNF), phospho‐cAMP response element‐binding protein (p‐CREB) and microRNAs may be important in regulating academic performance because of their roles in neuropsychiatry and cognitive diseases. The first goal of this study was to explore the associations among MeCP2, BDNF, CREB and academic performance. This study also examined the pathway responsible for the effects of MeCP2, BDNF, p‐CREB and microRNAs on academic performance. Scores from the basic competency test, an annual national competitive entrance examination, were used to evaluate academic performance. Subjects' plasma RNA was extracted and analyzed. This study determined that participants in the higher academic performance group had a significant difference in MECP2 mRNA expression compared with the lower academic performance group. We then used neuronal human derived neuroblastoma cell line (SH‐SY5Y) cells with inducible MeCP2 expression from a second copy of the gene as a gain‐of‐function model and found that MeCP2 overexpression positively affected p‐CREB and BDNF expression initially. After negative feedback, the p‐CREB and BDNF levels subsequently decreased. In the neuronal phenotype examination, we found a significant reduction in total outgrowth and branches in MeCP2‐induced cells compared with noninduced cells. This work describes pathways that may be responsible for the effects of MeCP2, BDNF, p‐CREB and microRNAs on academic performance. These results may shed light on the development of promising clinical treatment strategies in the area of neuropsychological adjustment. In this manuscript, the authors propose an interesting concept that plasma miRNA profiles might be indicative of academic performance and that these profiles might shed light on novel targets to manipulate for clinical treatment of neuropsychological conditions. Because microRNAs are not only present within cells but also circulate in the blood, they may become useful biomarkers of ID, cognition and neuropsychiatric disorders and guides for personalized learning, thereby enabling patient‐specific treatments and improved student learning. While the hypothesis is novel and interesting, the data provide little information beyond previously published works.